2012
DOI: 10.6061/clinics/2012(05)10
|View full text |Cite
|
Sign up to set email alerts
|

A comparative radiographic investigation of femoroacetabular impingement in young patients with and without hip pain

Abstract: OBJECTIVE:To compare the existence of radiographic abnormalities in two groups of patients, those with and without hip pain.METHODS:A total 222 patients were evaluated between March 2007 and April 2009; 122 complained of groin pain, and 100 had no symptoms. The individuals in both groups underwent radiographic examinations of the hip using the following views: anteroposterior, Lequesne false profile, Dunn, Dunn 45°, and Ducroquet.RESULTS:A total of 1110 radiographs were evaluated. Female patients were prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…While these studies suggest that cam deformities are rare in women, they are cross-sectional evaluations of asymptomatic patients and do not represent females who present with symptomatic impingement. Cam lesions can produce significant hip pain and motion restrictions ( 23 , 24 ), and Miguel et al have shown that symptomatic patients have significantly higher α angles compared to asymptomatic controls ( 25 ). Therefore, the prevalence of cam deformities in asymptomatic females may underestimate the prevalence of such deformities in those with symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…While these studies suggest that cam deformities are rare in women, they are cross-sectional evaluations of asymptomatic patients and do not represent females who present with symptomatic impingement. Cam lesions can produce significant hip pain and motion restrictions ( 23 , 24 ), and Miguel et al have shown that symptomatic patients have significantly higher α angles compared to asymptomatic controls ( 25 ). Therefore, the prevalence of cam deformities in asymptomatic females may underestimate the prevalence of such deformities in those with symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…This had led many clinicians to question the prevalence of FAI-related morphologic features in asymptomatic individuals [5,10,17,22,23,26,27]. Studies from Western countries have reported a relatively high prevalence of these findings-up to 66% [5,10,17,22,23,26,27,29]. Based on these studies, the emphasis is shifting to careful and prudent selection of surgical candidates for FAI.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these studies, the emphasis is shifting to careful and prudent selection of surgical candidates for FAI. Many clinicians agree that FAI is a clinical diagnosis and treatment decisions should not be made based on radiographic findings alone [2,29,32,33,36,39].…”
Section: Introductionmentioning
confidence: 99%
“…Little has been studied with regard to both the falseprofile view and the anterior CE angle. In a radiologic study comparing 2 cohorts of patients with asymptomatic and symptomatic hips, Miguel et al 19 noted no statistically significant difference between the groups when using the false-profile view and anterior CE angle criteria.…”
Section: Discussionmentioning
confidence: 99%